Ranacephala hogei (Mertens, 1967): new occurrence records, natural history, and subsidies for management and conservation status assessment - Assis, Clodoaldo Lopes de (2024)
Here we present the results of a long-term study on the threatened freshwater turtle Ranacephala hogei (Mertens, 1967). This species is endemic to the Atlantic Forest of southeastern Brazil and occurs in the states of Minas Gerais, Rio de Janeiro, and Espírito Santo. It inhabits the river basins of the Paraíba do Sul, Itapemirim, Lagoa Feia, and Córrego São Salvador. Ranacephala hogei is globally classified as Critically Endangered (CR) and is the only Brazilian chelonian included among the 25 most threatened turtle species worldwide. In addition, it is the first freshwater turtle species in Brazil selected for a captive management program. This prominence reflects the severe threats faced by the species, as its distribution is concentrated in some of the most densely populated regions of the country. Nevertheless, despite its high conservation relevance, R. hogei remains poorly studied, and even basic biological data are scarce. The lack of such information hampers conservation actions, compromises assessments of its conservation status, and weakens the efficient allocation of resources directed toward the species. In this context, we conducted a long-term study to update its geographic distribution and provide data on its natural history, with particular emphasis on coloration. Data collection began in 2016 and involved trapping, visits to scientific collections, literature review, citizen science, and spectrophotometric analyses. Among these approaches, citizen science proved to be particularly important, contributing the majority of occurrence records. Our results increased the number of known occurrence localities by 144%, totaling 45 localities for the species. These records expanded its known distribution, added a new river basin to its range, and revealed populations previously considered extinct. Spectrophotometric analyses showed that, despite its conspicuous appearance, the coloration of R. hogei provides effective camouflage in aquatic environments. The species also exhibits sexual and ontogenetic differences in brightness, with females being brighter than males. We further suggest that its shy behavior is associated with its conspicuous coloration. Overall, our findings provide valuable information that will contribute to future assessments of the conservation status of R. hogei and to the development of effective ex situ management strategies. Keywords: Atlantic Forest; distribution; coloration Chelidae; Testudines; conservation; geographic